2015
DOI: 10.1021/acs.joc.5b01332
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Thiele’s Acid Chemistry in Pursuit of a Suite of Conformationally Constrained Scaffolds

Abstract: The Diels-Alder dimer of cyclopentadiene carboxylate, Thiele's acid has conformational properties that make it attractive as a molecular scaffold for applications in supramolecular and biological chemistry. However, a lack of known reaction methodology for derivatives of Thiele's acid (or the corresponding esters) has hampered its utilization in these fields. We describe an improved preparation of Thiele's esters and survey the chemistry of these versatile intermediates. As part of this effort, we also describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…The heterodimerization of carboxylated cyclopentadiene and unmodified cyclopentadiene to give a mixture of regioisomers 3 and 4 is well known. 26 Building upon these earlier reports and taking advantage of our recently reported cyclopentadienylide salt-based route to ester-containing derivatives of dicyclopentadiene, 27 we were able to achieve the synthesis of 3 and 4 (in a ∼1.5:1 ratio) in 60% yield. The reaction behaved consistently upon scale-up and was easily increased to 45 g scale.…”
Section: Resultsmentioning
confidence: 76%
“…The heterodimerization of carboxylated cyclopentadiene and unmodified cyclopentadiene to give a mixture of regioisomers 3 and 4 is well known. 26 Building upon these earlier reports and taking advantage of our recently reported cyclopentadienylide salt-based route to ester-containing derivatives of dicyclopentadiene, 27 we were able to achieve the synthesis of 3 and 4 (in a ∼1.5:1 ratio) in 60% yield. The reaction behaved consistently upon scale-up and was easily increased to 45 g scale.…”
Section: Resultsmentioning
confidence: 76%
“…By contrast, the large variety of possible homo-and heterodimerization events that could potentially occur for species like 4A-C, coupled with the fact that the identities of the minor regioisomers resulting from dimerization (i.e. 2 and 3) were often incorrectly reported in the literature prior to our recent structural characterization efforts 6 (suggesting that the correct structures would not have been known to the earlier proponents of different predictive models) means that Thiele-type dimerizations can provide a uniquely effective testing set for the predictive power of various models. While we successfully exploited this testing set in our recent study 9 we also recognized that it would be more valuable if it could be expanded to include more regiochemical diversity.…”
mentioning
confidence: 96%
“…In previous synthetic work, we showed that cyclopentadiene esters dimerize analogously to cyclopentadiene carboxylates, affording an equivalent collection of regioisomers (i.e., 1b, 2b, and 3b) albeit with somewhat altered product ratios. 6 Ketones behave similarly, at least to the extent of producing major products analogous to 1. 6,14 In order to achieve different substitution patterns, we reasoned that we would have to employ more dramatically different electron-withdrawing groups.…”
mentioning
confidence: 99%
See 2 more Smart Citations